Let $f$ be a function $f:\mathbb R\to\mathbb R$.

Find all functions $f$ that satisfy:

$$f(x^2+x+3)+2f(x^2-3x+5)=x^2-x+ \frac{18}{4} + \frac{111}{444} + \frac{222}{333}$$

Maybe the question is wrong; I found it on a forum on the internet without any answers.

Note: The question has no solutions, I'm sorry. On the forum someone says he made it so probably there are no functions that satisfy this.

  • $\begingroup$ To be certain, is $lR$ the set of real numbers? $\endgroup$ – user714630 Sep 11 '13 at 1:09
  • 2
    $\begingroup$ Note that $(x-2)^2+(x-2)+3 =x^2-3x+5 $, so each polynomial on the left is the other shifted by $\pm 2$. This may be useful. I discovered this by noticing that the discriminants of the two are the same. $\endgroup$ – marty cohen Sep 11 '13 at 1:31
  • 3
    $\begingroup$ Is the RHS correct? If so, why is the constant coefficient written as $\frac{18}{4} + \frac{111}{444} + \frac{222}{333}$ rather than simply $\frac92 + \frac14 + \frac23 = \frac{65}{12}$? $\endgroup$ – Noam D. Elkies Sep 11 '13 at 2:01
  • $\begingroup$ yeah lR is the set of real numbers $\endgroup$ – Steve Sep 11 '13 at 11:55
  • 4
    $\begingroup$ Showing that there are no functions that satisfy this is just as interesting of a question as finding a function that does. No reason to apologize or delete the question. :) $\endgroup$ – apnorton Sep 11 '13 at 12:37

I continue from Christian's work.

Define $h(t) = g(t^2+2t)$ (so that $g(t)$ may be solved for by inverting the quadratic and taking suitable care). Then we have $$h(t) + 2h(-t) = t^2$$

Assuming we are interesting in $h$ which are infinitely differentiable at the origin, we can evaluate the $k$th derivative at the origin to obtain $$h^{(k)}(0)(1+2(-1)^k ) = 2\delta_{k,2}$$ or $$h^{(k)}(0) = \begin{cases} 0 & k\neq2 \\ \frac2 3 & k=2 \end{cases}$$ and so if we further consider functions which are analytic at the origin, we find $$h(t) = \frac 1 3 t^2$$

Then clearly if $x=t^2+2t$ we have $$t^2+2t-x=0 \iff t = -1 \pm \sqrt{1+x}$$

Hence $$g(x) = h(-1\pm\sqrt{1+x}) = \frac 1 3(\sqrt{1+x}\mp 1)^2=\frac 1 3 (2+x\mp 2\sqrt{1+x})$$

Finally, checking which signs work where, I find that $$\boxed{f(t)=\frac 1 {36} (41+12t-12\sqrt{4t-11}) \qquad\text{makes relation hold for}\qquad x \in \left(-\frac 1 2, \frac 3 2\right)}$$

The range has two ends because $f$ is evaluated at two places, and the solution breaks down where the sign changeover arises.

Note: This $g$ has series expansion agreeing with Christian's.

  • $\begingroup$ Super! (My coefficients are corrected now.) $\endgroup$ – Christian Blatter Sep 11 '13 at 17:58
  • $\begingroup$ @ChristianBlatter I've removed the comment :) $\endgroup$ – Sharkos Sep 12 '13 at 21:29

A beginning:

Write $x:={1\over2}+t$. Then your functional equation goes over into $$f\bigl({15\over4}+2t+t^2\bigr)+2f\bigl({15\over4}-2t+t^2\bigr)=t^2+{31\over6}\ .$$ Introduce a new unknown function $g$ by means of $$g(\tau):=f\bigl({15\over4}+\tau\bigr)-{31\over18}\ .$$ Then $g(0)=0$, and $g$ satisfies the functional equation $$g(2t+t^2)+2g(-2t+t^2)= t^2\ .$$ Writing $g(t)=\sum_{k=0}^\infty a_k t^k$ and comparing coefficients one obtains $$\eqalign{g(t)&={t^2\over12} - {t^3\over24} + {5 t^4\over192} - {7 t^5\over384} + {7 t^6\over512} - { 11 t^7\over1024} + {143 t^8\over16384} - {715 t^9\over98304} +\cr&\qquad { 2431 t^{10}\over393216} - {4199 t^{11}\over786432} + {29393 t^{12}\over6291456} - { 52003 t^{13}\over12582912} + {185725 t^{14}\over50331648}+\ldots\cr}$$ The series so produced seems to have a radius of convergence $>1$. At any rate one would have to look at the exact recursion formula for the coefficients.


It happens that this question is pure algebra...

No solution $f$ (whatever its regularity) can be defined on the five points $\frac{11}4$, $\frac{11}4\pm4$, $\frac{11}4\pm16$.

Consider the identity to be solved when the RHS is $x^2-x+c$, for some $c$ whose value will be irrelevant, and let $a=\tfrac34+c$. Some tedious but easy algebraic computations show that the sequence $(x_n)$ defined by $$ x_n=f\left(4n^2+\tfrac{11}4\right) $$ solves the identities $$ x_n+2x_{n-1}=4n(n-1)+a. $$ For example, $x_1=a-2x_0$, $x_2=8-a+4x_0$, $x_{-1}=\frac12a-\frac12x_0$ and $x_{-2}=4+\frac14a+\frac14x_0$.

By definition, $x_{-n}=x_n$ for every $n$, in particular, $$ a-2x_0=\tfrac12a-\tfrac12x_0,\qquad 8-a+4x_0=4+\tfrac14a+\tfrac14x_0. $$ The first identity implies that $a=3x_0$, and the second identity reads $4+\frac{15}4x_0=\frac54a$, which has no solution when the first identity holds since then, $\frac{15}4x_0=\frac54a$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.